Case report: hikikomori syndrome in Italy and its link with autistic traits and internet gaming disorder - Carpita, Barbara; Bonelli, Chiara; Giovannoni, Federico; Parri, Francesca; Gambini, Matteo; Nardi, Benedetta; Amatori, Giulia; Cremone, Ivan Mirko; Pini, Stefano; Dell’Osso, Liliana (Frontiers in Psychiatry, 2024)
During the last few decades, a growing field of literature is focusing on hikikomori, a phenomenon described as a form of pathological social withdrawal or social isolation that lasts for more than 6 months leading to significant functional impairment and/or distress. Despite initially considered a culture-bound syndrome, hikikomori syndrome later gained a wider recognition in different countries, ranging from an attempt to take refuge in an idealistic world, when society success’ standards are not reached, to a maladaptive coping strategy complicating several psychiatric illnesses such as anxiety disorders, major depression, internet addiction, internet gaming disorder (IGD) and autism spectrum disorder (ASD). In this framework, difficulties in social interaction, in problem solving strategies and socio-emotional reciprocity, may lead to social withdrawal and hikikomori-like behaviors. In this work, we described two cases of patients where the presence of underlying autism spectrum may have represented a sign of vulnerability towards the development of a possible full-blown case of hikikomori with IGD.